Smoking cessation and the reduction of disability progression in Multiple Sclerosis: a cohort study - Tanasescu, Radu; Constantinescu, Cris S.; Tench, Christopher R.; Manouchehrinia, Ali (Oxford University Press, 2018)
Background: Smoking is associated with a more severe disease course in people with multiple sclerosis (MS). The magnitude of effect of smoking cessation on MS progression is unknown. The aim of this study was to quantify the impact of smoking cessation on reaching MS disability milestones. Methods: This is a cross-sectional study with retrospective reports. A comprehensive smoking questionnaire was sent to 1270 patients with MS registered between 1994 and 2013 in the Nottingham University Hospital MS Clinics database. Demographic and clinical data were extracted from the clinical database. Cox proportional hazard regression was used to estimate effects of smoke-free years on the time to Expanded Disability Status Scale (EDSS) scores 4.0 and 6.0. MS Impact Scale 29 (MSIS-29) and Patient Determined Disease Steps (PDDS) were used to assess the physical and psychological impact of smoking. Results: Each ‘smoke-free year’ was associated with 0.96 (95% CI: 0.95 to 0.97) times decreased risk of reaching EDSS 4.0 and 0.97 (95%CI: 0.95 to 0.98) times decreased risk of reaching EDSS 6.0. Non-smokers showed a significantly lower level of disability in all the self-reported outcomes compared with current smokers. Conclusion: The reduction in the risk of disability progression after smoking cessation is significant and time-dependent. The earlier the patients quit, the stronger the reduction in the risk of reaching disability milestones. The quantitative estimates of the impact of smoking cessation on reaching disability milestones in MS can be used in interventional trials.